National stakeholder preferences for next-generation rotavirus vaccines: Results from a six-country study. Issue 2 (21st January 2022) - Price, Jessica; Mooney, Jessica; Bain, Carolyn; Bawa, John Tanko; Gurley, Nikki; Kumar, Amresh; Liyanage, Guwani; Mkisi, Rouden Esau; Odero, Chris; Seck, Karim; Simpson, Evan; Hausdorff, William P.
Highlights: An effective and affordable injectable rotavirus vaccine may be attractive to LMICs. Co-administering oral and injectable vaccines is acceptable to many stakeholders. Oral vaccine with a birth dose is favored over a higher cost, standalone injectable. Providing rotavirus vaccine in a DTP combination is the most preferred option. Abstract: Background: Currently available live, oral rotavirus vaccines (LORVs) have significantly reduced severe rotavirus hospitalizations and deaths worldwide. However, LORVs are not as effective in low- and middle-income countries (LMIC) where rotavirus disease burden is highest. Next-generation rotavirus vaccine (NGRV) candidates in development may have a greater public health impact where they are needed most. The feasibility and acceptability of possible new rotavirus vaccines were explored as part of a larger public health value proposition for injectable NGRVs in LMICs. Objective: To assess national stakeholder preferences for currently available LORVs and hypothetical NGRVs and understand rationales and drivers for stated preferences. Methods: Interviews were conducted with 71 national stakeholders who influence vaccine policy and national programming. Stakeholders from Ghana, Kenya, Malawi, Peru, Senegal, and Sri Lanka were interviewed using a mixed-method guide. Vaccine preferences were elicited on seven vaccine comparisons involving LORVs and hypothetical NGRVs based on information presented comparing the vaccines' attributes. Reasons for vaccine preference were elicited in open-ended questions, and the qualitative data were analyzed on key preference drivers. Results: Nearly half of the national stakeholders interviewed preferred a highly effective standalone, injectable NGRV over current LORVs. When presented as having similar efficacy to the LORV, however, very few stakeholders preferred the injectable NGRV, even at substantially lower cost. Similarly, a highly effective standalone injectable NGRV was generally not favored over an equally effective oral NGRV following a neonatal-infant schedule, despite higher cost of the neonatal option. An NGRV-DTP-containing combination vaccine was strongly preferred over all other options, whether delivered alone with efficacy similar to current LORVs or co-administered alongside an LORV (LORV + NGRV-DTP) to increase efficacy. Conclusion: Results from these national stakeholder interviews provide valuable insights to inform ongoing and future NGRV research and development.